Reusability Study of Steel Leaning Column Structure Utilizing Nonlinear Static Analysis - Ardianto, Johan (Jurnal Teknik Sipil, 2018)
Abstract: Two major earthquakes hit twoplaces in Indonesia in 2018, Palu city with 7.7 SR earthquake, and Lombok island by 6.4 SR earthquake. Many building especially concrete structure building got heavily damaged and even collapsing. Most of the damaged parts are the building’s beam-column joint, due to improper reinforcing. This damaged building is very difficult to repair due to disintegrated concrete. Thus, this building cannot be used anymore, and nothing can bedone except removing the remains and build a new structure. Because of this reason, this paper is studying a concept of reusability in structure, with the purpose to minimize structural damage in certain part of the building using leaner column theory. Leaning columns are columns that are pinned at each connection and provide no bending restraint in system. Theoretically leaning column cannot support axial and lateral loads, but since it is designed to lean on other structure, it can still resist the forces. Hence, this column is not suffering from lateral moment due to earthquake load, and the section is not exposed to damage. This paper is studying behavior of leaning column on exterior part of the structure with numerical simulation. Three-story building is modeled, one is with leaning column system, and the other is without leaning column. Performance-based design analysis with pushover method is carried. Result indicating that by using leaning column, exterior structure is not suffering from high moment when being hit byearthquake, and in other word, the exterior structure is not damaged when the earthquake comes and still can be used again.